(untitled) (Texas Journal of Medical Science, 2022)
According to the World Health Organization, regardless of the causes of portal hypertension syndrome (PG), it is one of the serious problems of pediatric surgery. In 80% of cases, children have extrahepatic PG (HSV) against the background of a developmental abnormality or portal vein thrombosis. PFA with PG in children are characterized by a sudden onset, high intensity and low effectiveness of conservative therapy